PEMANFAATAN MEDIA KOMUNIKASI WHATSAPP UNTUK MENGOPTIMALISASI KINERJA JURNALIS DITENGAH PANDEMI COVID-19. - I Ketut Manik Asta Jaya; Widya Duta (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2021)
This study aims to examine more deeply the benefits of Whatsappcommunication media to optimize the performance of journalists in themidst of the covid 19 pandemic. Especially now that the whole worldincluding Indonesia is still in the midst of the covid-19 pandemic, thusrequiring all activities to be limited while still implementing healthprotocols. In the midst of this condition, technological advances withvarious features are a solution to keep carrying out various activities,especially the profession as a journalist. This study uses a quantitativeapproach because it uses research strategies such as survey activities thatrequire statistical data. The results of this study indicate the high use of theWhatsapp application by respondents who are all journalists. In fact, oneof the results of the questionnaire distributed through Google Forms showsthat 100 percent of respondents choose the use of the Whatsappapplication compared to applications such as Facebook, Twitter, GoogleMeet and other applications. These results show that the Whatsappapplication supports the performance of journalists, especially in the midstof the covid 19 pandemic. In addition, the dominant respondents alsochoose the Whatsapp application to disseminate news links, compared tosocial media such as Facebook, Twitter and others. This result also causesmany features in the Whatsapp application that support performance as ajournalist. There are several features in the Whatsapp application: 1. Cansend text messages, 2. Receive and send photos from live cameras oralbums, 3. Send videos, 4. Exchange documents both in the form of filesand others and various other features.